Developing and Evaluating Capacity in Research and Development Organizations - Horton, Douglas; Alexaki, Anastasia; Bennett-Lartey, Samuel; Brice, Kim N.; Campilan, Dindo; Carden, Fred; Souza Silva, José de; Le Thanh Duong; Khadar, Ibrahim; Maestrey Boza, Albina; Kayes Muniruzzaman, Imrul; Perez, Jocelyn; et al. (International Service for National Agricultural Research, 2003)
The international aid community is placing a growing emphasis on developing the capacity of local organizations as the key to alleviating poverty and hunger in the developing world. Ensuring the effectiveness of a capacity building effort requires the appropriate use of evaluation. Yet few organizations have systematically monitored or evaluated organizational development processes. In January 2000, ISNAR began its ambitious ""Evaluating Capacity Development"" project, which aims to improve capacity development efforts in research and development organizations through evaluation. This Briefing Paper explains how the project used an action-learning approach, bringing together people from various countries and different types of organizations. These people conducted six evaluation studies over the course of three years, learning a great deal about capacity development and evaluation in the process. One of the key findings was the importance of involving staff and stakeholders in the evaluation process. A participatory approach fosters commitment to building the future of an organization and can speed up decision making. As people ""learn by doing"", they strengthen their own capacity for evaluation and are motivated to pass their knowledge on to others. When conducted in a participatory and structured way, evaluation can make a substantial contribution to improving overall organizational performance.